Free association versus juridification - Macnair, M (2011)
The last months of the outgoing Labour government and the creation of the Conservative-Liberal Democrat coalition have brought the question of the anti-union laws back into prominence. The recent, as it were 'traditional', left position on the issue is to call for the repeal of Thatcher and post-Thatcher anti-union laws. In practice, Labour left MPs and trade union leaderships have been promoting a much more limited body of technical amendments to the current legislation that would leave most of it in place. A minority view among pro-union lawyers is that what is needed is legal change to bring in a positive legal right to strike. This article argues that what is needed is neither merely the repeal of post-1979 laws, nor a 'positive right to strike'. The basis of the argument is that below the statute law is 'common law' unlawfulness of trade unions; and that this 'common law' unlawfulness is the product of severe judicial bias in the 'leading cases' in the early 18th and late 19th-early 20th centuries. I suggest that this judicial bias has an institutional basis, whose effect is that 'the rule of law' amounts to the dictatorship of the bourgeoisie. Hence, any proposals for reform of the anti-union laws need to be placed in the context of a more general political counter-offensive against juridification and the judicial power. © 2011 Critique.